Does return to work occur earlier after work-related sick leave episodes than after non-work-related sick leave episodes? A retrospective cohort study in Spain. Issue 1 (19th September 2008) - Benavides, F G; Serra, C; Domínguez, R; Martínez, J M; Plana, M; Despuig, M; Sampere, M; Gimeno, D
Abstract : Objective: In Spain, sick pay benefits for work-related sick leave episodes are higher than for non-work-related episodes. Our aim is to assess whether time to return to work is longer for higher paid sick leave episodes than for lower paid episodes. Methods: We used data from 62 376 work-related and 76 932 non-work-related sick leave episodes occurring among 338 226 workers from 56 099 companies in Spain in 2002. All episodes were followed for up to 18 months. Episodes were classified by a physician as being work- or non-work-related according to medico-legal judgments. The median episode duration and the 25th and 75th percentiles were calculated. The probability of remaining absent from work was estimated by a non-parametric estimator of the marginal survival function. The time ratio between both types of sick leave was estimated by a log-logistic regression model, using non-work-related episodes as the reference. Results: Median episode duration (25th–75th percentiles) was 11 (6–21) days for work-related episodes and 9 (4–29) days for non-work-related episodes. Time to return to work was longer for work-related episodes than for non-work-related episodes of less than 16 days (time ratio: 1.19 in men and 1.08 in women), while the opposite was observed for episodes of more than 15 days (0.58 in men and 0.40 in women). Conclusions: Sick pay benefits have a limited effect on time to return to work after a sick leave episode.